Structural analysis of absorber tube used in parabolic trough solar collector and effect of materials on its bending: A computational study. (15th March 2018) - Tripathy, Arun Kumar; Ray, Subhankar; Sahoo, Sudhansu S.; Chakrabarty, Shanta
Highlights: Temperature distribution, deflection, stress for PTSC tubes are obtained. Steel, copper, bimetallic and tetra layered laminate are used as tube materials. Temperature distribution, bending at various flow rates are calculated. Effects of self-weight on deflection of absorber tube are studied. Minimization of deflection obtained using a tetra layered laminate PTSC. Abstract: The maximum deflection of a Parabolic Trough Solar Collector (PTSC) absorber tube is a result of the circumferential non-uniformity in temperature distribution and self-weight. This non-uniformity in temperature is a factor of incoming solar flux distribution as well as material property of the absorber tube. The present work focuses on structural analysis of absorber tube used in PTSC and the effects of variations of material. Multiphysics platform, namely thermal-fluid analysis and structural analysis has been made in this regard. The computational investigation has been carried out on Schott PTR70 2008 receiver and Therminol VP1 as the Heat Transfer Fluid (HTF). Evacuated annular space along with specular and non-grey nature of glass cover which is semi-transparent to the input flux has been modeled to obtain better accuracy in results. The materials investigated are steel, copper, aluminum and various laminated composites like bimetallic (Cu-Fe) and tetra-layered laminate (Cu-Al-SiC-Fe), which are subjected to different mass flow rate of HTF at the absorber tube inlet with constant heat flux on the absorber tube outer surface. It is found that the change in the material of the absorber tube has a negligible effect on the amount of heat transferred to the HTF, but it has a significant effect on the bending due to thermal expansion as well as due to self-weight. Steel absorber tube is generally used, but its lower thermal conductivity results in poor circumferential temperature distributions. Copper has better thermal characteristics, but higher self-weight and lower mechanical strength compared to steel. So a combined effect of these properties is utilized in bimetallic tube, which results in a decrease in maximum deflection by 7–15% as compared to steel. As the self-weight of the absorber tube plays a vital role in deflection, therefore a tetra-layered laminate absorber tube having lower weight and improved temperature distribution results in a decrease in maximum deflection by 45–49% as compared to steel.